PENGOLAHAN HASIL PERTANIAN BUNGA GEMITIR SEBAGAI MASKER WAJAH KAYA ANTIOKSIDAN - L.P.F. Larasanty; N.L.P.V. Paramita; N.P.E. Leliqia; N.P.L. Laksmiani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Gemitir flower cultivation is one of the agricultural commodities in Apuan village, Susut district, Bangli. The demand for gemitir flowers fluctuates from time to time. When prices are low, farmers will generally experience losses. It is necessary to carry out community service activities that aim to diversify gemitir flower agricultural products into cosmetic products in the form of natural face masks with high antioxidant content. Gemitir flower petals are known to contain tagetin and hydroxyflavones which are naturally antioxidants and are useful in the process of skin regeneration. This face mask product can become a processed product that provides more economic value for farmer groups in Apuan Bangli Village. Community service activities are carried out in stages starting with a survey at the location of the service to see when the gemitir flowers are harvested. At harvest time, the flowers that have bloomed are then collected as needed to be used as samples for processing into face masks. In the first step, the activities carried out were the process of selecting and drying flowers in a natural way and with the help of an oven, then they were made into powder. Product manufacturing activities begin with the pre-formulation of mask preparations. Then with the existing formula, training activities on how to make masks were carried out, including mask packaging. The results of monitoring and evaluation activities showed an increase in public knowledge with an initial average value of 28 to 71 after the final monitoring evaliation was carried out. Keywords: gemitir flower, face mask, natural, antioxidant, training.